Evaluation of the impact of the first evidence-based guidelines for congenital toxoplasmosis in Armenia (Quindío) Colombia: An observational retrospective analysis - Manuela Mejia-Oquendo; Elizabeth Marulanda-Ibarra; Jorge Enrique Gomez-Marin (Elsevier, 2021)
Background: Colombia implemented the world's first evidence-based guidelines for congenital toxoplasmosis in 2013, no evaluation of its impact has been reported. Methods: We reviewed the clinical charts of cases referred to the specialized consultation of the health care centre at Universidad del Quindío during an 18-year period (2001-2019), where the diagnosis criteria and the correlation between prenatal treatment and symptoms at birth were analysed. Additionally, we described the diagnosis criteria and treatment for mothers during pregnancy at a primary prenatal care centre in the city of Armenia during 2018. Institutional consent was obtained to review clinical charts. Findings: At the referral centre, we found that before the implementation, 27.3% did not have prenatal diagnosis but after implementing the clinical practice guidelines, all mothers were diagnosed during pregnancy. In addition, we observed that prenatal treatment was associated with fewer symptoms and this improved significantly over time after implementing the guidelines. At the primary health care centre in 2018, we found that all mothers were diagnosed and treated, as recommended by the national guideline. Interpretation: The national guideline has had a positive impact by improving early diagnosis and treatment of prenatal toxoplasmosis and reducing severe forms, as observed at the referral centre. Funding: Colombian Ministry of Science.